An investigation on emotional intelligence of students with respect to student development model and its implication on emotional learning system in Malaysia - Sanjeevkumar, Virmala (2012)
We human being have different personalities, different wants and needs, and different ways of showing our emotions. Navigating though this all takes tact and cleverness - especially if we hope to succeed in life. This is where emotional intelligence becomes important. Emotional intelligence is the ability to recognize your emotions, understand what they're telling you, and realize how your emotions affect people around you. Emotional intelligence also involves your perception of others: when you understand how they feel, this allows you to manage relationships more effectively. This research study presents a framework for emotional intelligence, a set of skills hypothesized to contribute to the accurate appraisal and expression of emotion in oneself and in others, the effective regulation of emotion in self and others, and the use of feelings to motivate, plan and achieve in one's life. This review examines the foundations of the definitions of emotional intelligence as well as existing educational research involving emotional intelligence, within the students in Malaysia. Recommendations for future research and research potential are discussed. From this study we probably also know students who are masters at managing their emotions. Regardless of their strengths, however, they're usually willing to look at themselves honestly. They take criticism well and they know when to use it to improve their performance. People like this have a high degree of emotional intelligence, or El. They know themselves very well, and they're also able to sense the emotional needs of others. Thus this study gives a deep insight about Emotional Intelligence among students in Malaysia.